THE EFFECT OF SUPPLY CHAIN MANAGEMENT PRACTICES AND INFORMATION AND COMMUNICATION TECHNOLOGY ON COMPETITIVE ADVANTAGE AND FIRM PERFORMANCE (CASE STUDY: SMEs OF PROCESSED FOOD IN JAKARTA) - Jumady Sinaga; Elisa Anggraeni; Alim Setiawan Slamet (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Micro, Small, and Medium Enterprises' (SMEs) development will strengthen domestic economic structure due to the workforce absorption and increase people's purchasing power, the level of demand, and investment growth. Although it has a very strategic role, developing SMEs is not simple. As time goes by, the trend of SMEs selling products online is increasing. Competition is getting tougher, and product innovation is increasingly diverse. Thus, to improve overall performance, SME players must compete to implement strategies. This research aimed to analyze the effect of supply chain management practices on competitive advantage and firm performance, communication, and information technology on supply chain management practices and competitive advantage, and competitive advantage on fir performance. The questionnaires were distributed online to processed food SMEs in Jakarta, using a simple random sampling technique. The samples collected were 244 respondents, and it was analyzed using Structural Equation Modeling (SEM). The results showed that supply chain management practices had a positive effect on competitive advantage. Communication and information technology had a positive effect on supply chain management practices and competitive advantage, and competitive advantage had a positive effect on firm performance. Keywords: competitive advantage, firm performance, ICT, Structural Equation Modeling, supply chain management practices